Sustenance strategies for lean manufacturing implementation in Malaysian manufacturing industries - Norhana, Mohd Aripin; Nawanir, Gusman; Suhaidah, Hussain (2022)
This study aims to investigate the relationship between sustaining factors and lean manufacturing implementation.This survey-based study was a cross-sectional study and the samples were drawn by using cluster sampling procedure from medium and large manufacturing companies based on the Federation of Manufacturers Malaysia (FMM) with the final number of 151 respondents. In total, four hypotheses were developed and tested statically using PLS-SEM through SmartPLS software.The result provided evidence that lean culture, lean leadership, and lean knowledge management have a positive relationship on lean manufacturing implementation. However, lean supplier management does not have a positive relationship on lean manufacturing implementation.The survey was responded by middle and top-level management from the discrete manufacturing industries. Although there is growing interest in empirical shreds of evidence in favor of sustaining lean, this study provides a comprehensive view of sustaining factors for lean manufacturing implementation.Hence, this study contributes to expanding the boundary of the existing literature and contributes to the body of knowledge while providing insights to practitioners in tailoring strategies to sustain lean manufacturing implementation and leverage their performance.